207k views
1 vote
Multiply. (3x - 2)(x + 5) A: 3x² + 17x - 7 B: 3x² + 17x - 10 C: 3x² + 13x - 10 D: 3x² + 6x - 7

2 Answers

4 votes

Answer:

C. 3x^2+13x-10

Explanation:

Just did this on A-pex

Good job CHERLYN

User Mayur Tolani
by
4.5k points
2 votes

Answer:

The answer is C.

Explanation:

You have to use Ditributive Law,


a(m + n) = am + an

So for this question :


(3x - 2)(x + 5)


= 3x(x) + 3x(5) - 2(x) - 2(5)


= 3 {x}^(2) + 15x - 2x - 10


= 3 {x}^(2) + 13x - 10

User Knetsi
by
5.1k points